HUBUNGAN PENGETAHUAN DAN EKONOMI TERHADAP PEMILIHAN KONTRASEPSI IUD PADA WUS DI DESA BULUSULUR WONOGIRI - Kristiningtyas, Y. Wahyunti; Triwahyuniastuti, Triwahyuniastuti (Jurnal AKPER GSH, 2018)
Family planning is an effort to regulate population. Family planning is the use of fertilization regulating methods to help a person or family achieve certain goals. The purpose referred to here is an arrangement of pregnancy deliberately by the family and for the welfare of the family. To achieve the success of family planning services, it is necessary to be supported by the community as supporters of the family planning movement by actively participating as family planning participants or family planning acceptors. There are many factors that influence the choice of contraception, including partner factors, health factors, contraceptive method factors, education level, knowledge, family welfare, religion, and support from husband / wife. These factors will also influence the success of the family planning program. This is because each method or method of contraception chosen has different effectiveness. The purpose of this study was to determine the relationship between knowledge and economy on the choice of IUD contraception in Bulusulur Village, Wonogiri District, Wonogiri Regency. This type of research is an analytic survey with a cross sectional approach. The population in this study were all women of childbearing age in RW 09 Bulusari, Bulusulur Wonogiri as many as 91 people. The sample in this study were all women of childbearing age in RW 09 Bulusari, Bulusulur Wonogiri as many as 91 people. The instrument used in this study was a questionnaire to measure the level of knowledge and economy of WUS about the IUD. The data analysis used was univariate analysis to determine the frequency distribution of each variable and bivariate analysis using the Chi Square test to determine the relationship between the independent variable and the dependent variable. The results showed that most (54.9%) women of childbearing age in RW 09 Bulusulur Wonogiri had good knowledge and 50.5% had high economic status. The results of the analysis show that there is a significant relationship between knowledge and IUD contraceptive selection (p value = 0.001) <0.05 and there is a significant relationship between economy and IUD contraceptive selection (p value = 0.001) <0.05 in women of reproductive age in RW 09 Bulusulur Village Wonogiri.